Who leaves and when? Selective outmigration of immigrants from Germany - Torben Kuhlenkasper; Max Friedrich Steinhardt (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
The paper provides new evidence on the outmigration of foreign-born immigrants. We make use of data from the German Socio-Economic Panel and employ penalised spline smoothing in the context of a Poisson-type Generalised Additive Mixed Model (GAMM), which enables us to incorporate bivariate interaction effects. A unique feature is the use of data from dropout studies to identify outmigration. For Turkish immigrants, outmigration is characterized by positive skill selection intensifying the initial negative selection process. For Non-Turkish immigrants we instead find a u-shaped pattern between human capital and outmigration. Finally, we discover substantial variation in emigration behaviour during the life-cycle.
Keywords: C14; C51; F22; J61; 330; emigration; self-selection; German Socio-Economic Panel; generalised additive mixed models; Auswanderung; Ausländer; Rückwanderung; Migranten; Schätzung; Deutschland